Control of depositional and diagenetic processes on the reservoir properties of the Mishrif Formation in the AD oilfield, Central Mesopotamian Basin, Iraq. (October 2021) - Wang, Huan; Shi, Kaibo; Ma, Yongsheng; Liu, Bo; Song, Xinmin; Ge, Yuzhu; Liu, Hangyu; Hoffmann, René; Immenhauser, Adrian
Abstract: The results of a multiproxy study on Mishrif carbonates from the margins of the Central Mesopotamian Basin of Iraq display a wide range of rock fabrics and diagenetic features, all affecting reservoir quality and flow properties in a complex manner. Based on petrographic and facies analyses of the Mishrif Formation in the AD oilfield, the model of a homoclinal ramp geometry with twelve characteristic microfacies types is proposed. A relevant observation is that the ramp, judging from the core data of the AD oilfield studied here, reflects low-energy conditions as documented by an abundancy of fine-grained carbonates in nearly all microfacies types. This notion is perhaps best understood in the context of an intrashelf basin with significant wave-seafloor interaction leading to wave degradation and a shallow effective wave base. In contrast to the rudist bioherms that typify the more basin-marginal settings, we find mainly evidence for small, low-relief buildups characterized by green algae. The Mishrif reservoir properties are shaped by two main diagenetic features: (i) early diagenetic, aquifer-related marine-meteoric mixing zone dissolution inducing abundant fabric selective porosity and (ii) the preferential cementation of Thalassinoides burrows leading to low-porosity concretionary carbonate nodules with reservoir properties that differ significantly from those of the host carbonate. Given the somewhat more distal position of the AD oilfield, the effects of prolonged stages of subaerial exposure related to sea-level fall, as reported from more basin marginal settings, are not recognized. The bending and splaying of seams around nodules and the well-preserved skeletal material within these concretionary carbonates demonstrate that the onset of nodule cementation was early diagenetic/pre-compactional in nature. Based on integrated microfacies and reservoir properties, seven rock types (i.e., Rock Type I-VII) with distinctive reservoir qualities are recognized. Nodular concretions are mainly developed in the Rock Type I lithology and result in distinctive cm-to dm-scale heterogeneity. The contrast between small, poorly-connected pore systems in nodules and medium-sized, well-connected pore systems in the host rock are best described as an inconspicuous, dual permeability system. Data shown here and evidence from other studies dealing with the Mishrif in the Central Mesopotamian Basin are important to understand and predict reservoir properties in other carbonate fields with similar properties. Highlights: The Lower Mishrif in Iraq was deposited on a low-energy homoclinal ramp. A genetic model to explain the relationship between bioturbation and concretion, and their impact on reservoir properties. Seven reservoir types with distinctive porosity system are recognized based on microfacies and reservoir property.